The Effect of Using Roger Bybee Model on Understanding Arithmetic Operations on Regular Fractions and Decimals for sixth Graders - Adnan Al Abed; Mohammed Al Baba (Deanship of Scientific Research (DSR), the University of Jordan, 2020)
This study aims to reveal the effect of using Roger Bybee model on the comprehension of arithmetic operations on regular fractions and decimals for sixth graders. The sample of the study was selected in an intentional method.  Random assignment was applied to distribute the sample into two groups: an experimental group consisting of (37) students who were taught using Roger Bybee model, and a control group consisting of (37) students who were taught using the usual method. Teaching material for the unit "Regular Fractions and Decimals" for the sixth grade was prepared according to the Roger Bybee model, and its validity was verified. Two tests were also prepared. The first is to understand arithmetic operations on regular fractions, and the second is to understand arithmetic operations on decimals. The results showed that there were statistically significant differences in favor of the experimental group in each of the comprehension of arithmetic operations on ordinary fractions and decimals.